The effects of zinc and melatonin on muscle ischaemi-reperfusion injury in rat - Celer, Mehmet; Mogulkoc, Rasim; Baltaci, Abdulkerim Kasim; Dasdelen, Dervis (Cellular and Molecular Biology, 2018)
Ischemia-reperfusion leads to damage in cell or tissue due to insufficient blood flow. The aim of present study was to determine the effect of zinc, melatonin and zinc + melatonin supplementations during 3 weeks on muscle tissue and plasma MDA and GSH levels. This study was performed on 38 male Wistar-Albino rats. Experiments groups were designed as sham-control, ischemia-reperfusion (I/R), zinc + I/R, melatonin + I/R and zinc + melatonin + I/R Ischemia-reperfusion was induced by left femoral artery occlusion (1 hour) and reopening (1 hour). At the end of experiments tissue and blood samples were analysed for MDA and GSH. MDA levels were increased, GSH levels decreased in I/R groups. However, zinc and melatonin supplementation inhibited MDA and increased GSH levels in I/R groups. The results of present study show that increased lipid peroxidation in muscle tissue by ischemia-reperfusion may be prevented by zinc and melatonin or zinc plus melatonin supplementation.